Code Switching Found in Cinta Laura on Program Trans TV Youtube Channel - I Komang Sulatra; Ida Bagus Gde Nova Winarta; Satyawati, Ni Putu (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
This study aimed (1) to find out the types of code switching found in Cinta Laura’s utterances on Deddy's corner program in Trans TV and (2) to analyse the reason of code switching found in Cinta Laura’s utterances on Deddy's corner program in Trans TV. The data were utterances spoken by Cinta Laura in four videos taken from Trans TV Youtube Channel. This study used qualitative method in analysing the data. The data were collected by observation method through watching, listening and transcribing the utterances. There were two basic theories used in this study. The first theory is taken from Poplack (1980) about types of code switching and the second theory is taken from Hoffman (1991) about reasons of code switching. The result of the study shows 23 utterances of code switching. Those are intra-Sentential switching with ten 10 utterances with percentage 43,5%, 9 data of extra-sentential switching or tag switching with percentage 39,13%, 4 data of inter-sentential switching with percentage 17,39%. The most dominant reason is interjection (inserting sentence filler and sentence connector), the second reason of being emphatic about something, the third is talking about particular topic, the lowest occurrence of the reason was repetition used for clarification and intention of clarifying speech content.